Sunny Chandler's return [compact disc, unabridged] - Brown, Sandra, 1948- (Books on Tape, 2003)
Rumors abound when Sunny Chandler makes an appearance in her hometown to attend her best friend's wedding. She's passed the last three years in New Orleans, and her sophisticated new look catches the eye of everyone she meets--especially Ty Beaumont, the town's sexy sheriff.